2021
DOI: 10.3390/horticulturae7120567
|View full text |Cite
|
Sign up to set email alerts
|

UV-B Radiation as Abiotic Elicitor to Enhance Phytochemicals and Development of Red Cabbage Sprouts

Abstract: Background: The main objective of this study was to evaluate the effect of periodical UV-B illumination during red cabbage germination on morphological development and the phenolics and carotenoid accumulation. Methods: During a sprouting period of 10 days at 20 °C in darkness, seedlings received 5, 10, or 15 kJ m−2 UV-B (T5, T10, and T15) applied in four steps (25% on days 3, 5, 7, and 10). UV untreated sprouts were used as control (CTRL). After 10 days of germination, the sprouts were harvested and stored 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 55 publications
0
5
1
Order By: Relevance
“…Carotenoids are known to be strong antioxidants and are involved in plant photoprotection, playing a central role in the dissipation of excessive light energy [95]. Many studies have found a stimulatory effect of UV on carotenoids, suggesting a conserved response [6,26,44,45,96]. However, the results of this study showed that carotenogenesis was not affected immediately after the application of a low dose of UV.…”
Section: Uv Enhances the Synthesis Of Short-chain Rather Than Long-ch...contrasting
confidence: 63%
“…Carotenoids are known to be strong antioxidants and are involved in plant photoprotection, playing a central role in the dissipation of excessive light energy [95]. Many studies have found a stimulatory effect of UV on carotenoids, suggesting a conserved response [6,26,44,45,96]. However, the results of this study showed that carotenogenesis was not affected immediately after the application of a low dose of UV.…”
Section: Uv Enhances the Synthesis Of Short-chain Rather Than Long-ch...contrasting
confidence: 63%
“…The determination of TPC was carried out according to the method described by Singleton and Rossi [7] with some modifications by Martínez-Zamora et al [8]. The TPC was calculated using a gallic acid standard and expressed as g of gallic acid equivalent per kg of dried weight (g GAE/kg dw).…”
Section: Total Polyphenolic Contentmentioning
confidence: 99%
“…Total antioxidant capacity was determined through the free radical scavenging capacity generated by DPPH• and ABTS+. In the DPPH assay [12] , 194 μL of DPPH• solution was added to 21 μL of sprout extract [13] in a 96-well plate. The mixture was incubated for 30 min at room temperature in the dark.…”
Section: Determination Of Total Antioxidant Capacitymentioning
confidence: 99%
“…The ABTS assay was performed following the method described by Martínez-Zamora et al [14] . For this, 200 μL of activated ABTS + solution (32 µM) was added to 11 μL of sprout extract [13] in a 96-well plate, incubated for 20 min at room temperature in the dark, and changes in absorbance at 414 nm were measured. Each sample was analyzed in triplicate.…”
Section: Determination Of Total Antioxidant Capacitymentioning
confidence: 99%